Three phase z-source neutral point clamped inverter with multicarrier PWM technique. Issue 5 (5th September 2016) - Edwin Deepak, F.X.; Rajasekaran, V.
Abstract : Purpose: The purpose of this paper is to present the three phase seven-level Z-source neutral point clamped (NPC) inverter with multicarrier pulse-width modulation (PWM) technique. Despite numerous topologies and modulation methods, there is a dire need of developing PWM techniques that can be deployed in multilevel inverters. These inverters decrease the total harmonic distortion and it has a good performance for various electrical power system applications. The proposed inverter is investigated for its performance by executing it in shoot through and non-shoot through modes. Design/methodology/approach: The purpose is validated through MATLAB/Simulink software platform for implementing the proposed seven-level Z-source NPC inverter outlined with multicarrier based phase disposition technique. The experimental results are verified using SPARTAN 3E FPGA controller with the same control strategy. Findings: The efficiency of the proposed inverter is confirmed in terms of increased and faster conversion in the shoot-through mode. By using PDPWM technique the maximum boost gain is achieved with lower modulation index. High control of DC voltage is obtained with only one DC voltage source and one Z network. Originality/value: Three phase multilevel inverters are widely used in improving the output voltage quality and reducing the encountered electromagnetic interference in electronic device or circuitry. They are employed in medium and high –power applications to attain increased power ratings while decreasing the switching losses. The performance results shown in this paper will satisfy the above needs of usage in certain applications and less switching losses.